Sobre unes frases relatives sense antecedent - Bartra i Kaufmann, Anna (Caplletra. Revista Internacional de Filologia, 2015)
In this paper a new analysis of some free relative sentences as selected CPs is proposed. These CPs have a [+WH] phrase in [SPEC, C’] which heads an A’ chain. This A’ chain is responsible of the NONSPECIFIC ARGUMENT interpretation of the sentence. I argue that this analysis has several theoretical and descriptive advantages over the classical one, which treats the sentences as headless relatives.